Glutathione responsive chitosan-thiolated dextran conjugated miR-145 nanoparticles targeted with AS1411 aptamer for cancer treatment. (1st December 2018) - Tekie, Farnaz Sadat Mirzazadeh; Soleimani, Masoud; Zakerian, Amir; Dinarvand, Meshkat; Amini, Mohsen; Dinarvand, Rassoul; Arefian, Ehsan; Atyabi, Fatemeh
Graphical abstract: Highlights: TD-miR redox responsive conjugates and PECs ensure miRNA stability against nucleases. Nano PECs were easily obtained by electrostatic complexation of TD-miR and chitosan. TD-miR and PECs could transfer anti-tumor miR-145 and suppress cell proliferation. PEC(18, 5) and targeted nano PECs with AS1411 are the most appropriate formulation. apt-PECs as dual targeted nanoparticles are useful for both chemo/bio-drug delivery. Abstract: miR-145 is a tumor suppressive miRNA which is abnormally reduced in different cancers. miR-145 overexpression reduces cancer migration, invasion, and cell adhesion. Increasing miR-145 level using suitable and efficient gene delivery systems could be valuable in cancer treatment. In this study, a redox-responsive miR-145 conjugated thiolated dextran (TD-miR) was prepared. Also, polyelectrolyte complexes (PECs) of TD-miR and chitosan were fabricated and decorated with anti nucleolin aptamer, AS1411 (apt-PEC). The size of the PECs was between 40–270 nm, and the zeta potential was varied according to the TD-miR to chitosan molar ratio. The outcomes of cellular studies indicated the excellence of the apt-PEC as a duel targeted delivery system and the PECs composed of chitosan 18 kDa with TD-miR to chitosan ratio of 5. TD-miR and the PECs are appropriate as the smart gene delivery systems which preserve and transfect the cargo and release it in cytoplasm.